2021
DOI: 10.1002/hep.31745
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box 1 Release by Cholangiocytes Governs Biliary Atresia Pathogenesis and Correlates With Increases in Afflicted Infants

Abstract: These results suggest that HMGB1 plays a role in virus induced BA pathogenesis and could be a target for therapeutic interventions in a subset of patients with BA and high HMGB1. (Hepatology 2021;74:864-878). B iliary atresia (BA) is a disease of infancy in which a devastating fibroinflammatory cholangiopathy occurs, leading to obstructive jaundice. BA leads to end-stage liver disease (ESLD). (1)(2)(3)(4) In the United States, the incidence of BA is 1 in 15,000 births, (5) and it is the most common indication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
(86 reference statements)
1
26
0
Order By: Relevance
“…They conduct extracellular signals through a tertiary kinase cascade, specifically, extracellular signal → MAPK kinase (MKKK) → MAPK kinase (MKK) → MAPK 127 . MAPK family members divergently contribute to HMGB1 release in different inflammatory and injury models 128 131 . For example, the expression and release of HMGB1 is mediated through the p38 MAPK signaling pathway induced by rhesus rotavirus, while inhibition of p38 prevents HMGB1 release in cholangiocytes 131 .…”
Section: Active Hmgb1 Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…They conduct extracellular signals through a tertiary kinase cascade, specifically, extracellular signal → MAPK kinase (MKKK) → MAPK kinase (MKK) → MAPK 127 . MAPK family members divergently contribute to HMGB1 release in different inflammatory and injury models 128 131 . For example, the expression and release of HMGB1 is mediated through the p38 MAPK signaling pathway induced by rhesus rotavirus, while inhibition of p38 prevents HMGB1 release in cholangiocytes 131 .…”
Section: Active Hmgb1 Secretionmentioning
confidence: 99%
“…MAPK family members divergently contribute to HMGB1 release in different inflammatory and injury models 128 131 . For example, the expression and release of HMGB1 is mediated through the p38 MAPK signaling pathway induced by rhesus rotavirus, while inhibition of p38 prevents HMGB1 release in cholangiocytes 131 . MAPK-mediated HMGB1 secretion is also implicated in endothelial inflammation, thus providing a potential therapeutic strategy for vascular diseases 132 .…”
Section: Active Hmgb1 Secretionmentioning
confidence: 99%
“…Inflammation is intimately associated with BA. In a recent report, RRV infection in mice was shown to cause increased expression and release of the protein HMGB1, which has been implicated in mediating inflammation [71] . HMGB1 induction was mediated via the p38 MAPK signalling pathway, which offers potential therapeutic opportunities.…”
Section: Novel Insights Into Biliary Atresia Pathomechanismsmentioning
confidence: 99%
“…
<FNTX>Abbreviations: BA, biliary atresia; HMGB1, high mobility group box protein 1; ICO, human cholangiocyte organoid<FNTX> With great interest, we read the study by Mohanty S et al (1) demonstrating that rotavirus-infected cholangiocytes actively release high mobility group box protein 1 (HMGB1), contributing to the pathogenesis of biliary atresia (BA). The activation of HMGB1 secretion involves viral induction of reactive oxygen species and is mediated by the p38/STAT1 axis.
…”
mentioning
confidence: 99%
“…Immunosuppression agents, such as corticosteroids, have been applied to confine inflammation during the Kasai procedure but showed contradictory results. (1) Mohanty et al (1) now identified serum HMGB1 as a non-invasive biomarker, possibly reflecting "the right window" for anti-inflammatory therapy. This novel insight may also help to stratify BA patients together with histological scoring approaches and molecular signatures, such as inflammatory, virus, fibrotic, and cell death-related markers, to improve the therapeutic effect.…”
mentioning
confidence: 99%